2007
DOI: 10.1007/s00420-007-0216-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of two types of chromium exposure in an electroplating shop

Abstract: Although uncorrelated with soluble Cr(VI), urinary Cr (24 h) is effectively related to the soluble fraction of airborne chromium. In the case of chromium electroplating, correspondence between exposure and excretion appears to be governed by relationships different to those emerging from stainless steel welding, from which current biological limit values have been derived.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…1,2,18 Cr-U at ES closely correlated with Cr-P, which in turn correlated with Cr-RBC, whereas the correlation between Cr-U and Cr-RBC was not significant. Despite the expected differences due to the type of exposure, 35 these data are in line with those recently found by Scheepers et al (2008), who observed that Cr-P in welders exposed to low levels of Cr(III) and Cr(VI) closely correlated with Cr-U at both BS and ES, and that the correlation between Cr-RBC and Cr-U was significant, although the correlation coefficient was lower. 36 On the other hand, the correlation between Cr-P and Cr-U/Cr-RBC was lost in BS samples, in which only the correlation between Cr-U and Cr-RBC was highly significant.…”
Section: Discussionsupporting
confidence: 91%
“…1,2,18 Cr-U at ES closely correlated with Cr-P, which in turn correlated with Cr-RBC, whereas the correlation between Cr-U and Cr-RBC was not significant. Despite the expected differences due to the type of exposure, 35 these data are in line with those recently found by Scheepers et al (2008), who observed that Cr-P in welders exposed to low levels of Cr(III) and Cr(VI) closely correlated with Cr-U at both BS and ES, and that the correlation between Cr-RBC and Cr-U was significant, although the correlation coefficient was lower. 36 On the other hand, the correlation between Cr-P and Cr-U/Cr-RBC was lost in BS samples, in which only the correlation between Cr-U and Cr-RBC was highly significant.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies of electroplating workers have often reported poor/no correlations between air and urine metal concentrations 18-20 , although some studies have observed moderate to high correlations (range: r = 0.48–0.96, median: r = 0.68) 21-24 . The relationship between air and urinary measurements likely varies due to the extent of dermal exposure, the use of personal protective equipment, and personal behaviors such as smoking that may transfer the contaminants from hand to mouth, as well as the time of day the urinary measurements are collected in relation to the air measurements 21-22, 25-26 .…”
Section: Introductionmentioning
confidence: 97%
“…(96) As already mentioned, Pierre et al (1998) studied the individual exposure and plasma and urine levels of aluminium for 335 workers from seven aluminium industry plants. Detailed air and urine data are provided for six individuals monitored over 1 week (Table 6.4).…”
Section: Ingested Materials ômentioning
confidence: 99%